Towards a definition of a business performance measurement system - Franco-Santos, Monica; Kennerley, Mike; Micheli, Pietro; Martinez, Veronica; Mason, Steve; Marr, Bernard; Gray, Dina; Neely, Andrew (Emerald Group Publishing Limited, 2007)
Scholars in the field of performance measurement tend to use the term business performance measurement (BPM) systems without explaining exactly what they mean by it. This lack of clarity creates confusion and comparability issues, and makes it difficult for researchers to build on one an each other's work. The purpose of this paper is to identify the key characteristics of a BPM system, by reviewing the different definitions of a BPM system that exist in the literature. This work aims to open a debate on what are the necessary and sufficient conditions of a BPM system. It is also hoped that a greater level of clarity in the performance measurement research arena will be encouraged. Design/methodology/approach--The performance measurement literature is reviewed using a systematic approach. Findings--Based on this research, a set of conditions of a BPM system has been proposed from which researchers can choose those which are necessary and sufficient conditions for their studies. Research limitations/implications--The analysis in this paper provides a structure and set of characteristics that researchers could use as a reference framework to define a BPM system for their work, and as a way to define the specific focus of their investigations. More clarity and precision around the use of the BPM systems phrase will improve the generalisability and comparability of research in this area. Originality/value--By reviewing the different definitions of a BPM system that exist in the literature this paper will hopefully stimulate a debate on the necessary and sufficient conditions of a BPM system and encourage a greater level of clarity in the performance measurement research arena.
Keywords: Business performance; Performance management; Performance measurement (quality)